Genetic basis of cytokinin and auxin functions during root nodule development - Suzaki, Takuya; Ito, Momoyo; Kawaguchi, Masayoshi (Frontiers in Plant Science, 2013)
The phytohormones cytokinin and auxin are essential for the control of diverse aspects of cell proliferation and differentiation processes in plants. Although both phytohormones have been suggested to play key roles in the regulation of root nodule development, only recently, significant progress has been made in the elucidation of the molecular genetic basis of cytokinin action in the model leguminous species, Lotus japonicus and Medicago truncatula. Identification and functional analyses of the putative cytokinin receptors LOTUS HISTIDINE KINASE 1 and M. truncatula CYTOKININ RESPONSE 1 have brought a greater understanding of how activation of cytokinin signaling is crucial to the initiation of nodule primordia. Recent studies have also started to shed light on the roles of auxin in the regulation of nodule development. Here, we review the history and recent progress of research into the roles of cytokinin and auxin, and their possible interactions, in nodule development.